FAKTOR-FAKTOR PENDORONG PERILAKU KONSUMTIF MAHASISWA PENDIDIKAN EKONOMI TERHADAP E-COMMERCE: Studi Kualitatif di UM Palangkaraya - Arna Purtina (FKIP Unswagati, 2025)
Technology is currently developing rapidly and has an impact on society. With this sophistication, various sites have emerged, one of which is a buying and selling site that is very easy to access with the palm of your hand via smartphone. The relatively frequent intensity of use ultimately results in transactions that are not in accordance with the plan. This study aims to determine the factors driving consumer behavior of economic education towards e-commerce. This study is a qualitative descriptive study with primary data directly from key informants in the form of observations and interviews. The determination of informants used was Snowball Sampling with the number of informants being 3 students of the 2023 class of the Economic Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Palangkaraya. The results of the study show that the factors driving consumer behavior of economic education students towards e-commerce are 1). Internal factors: a. Lifestyle (Lifestyle), b. Desire for existence (self-image), c. Poor financial management, d. Emotions and psychology. 2). External factors: a. Discounts, proms, and cashback, b. Advertisements and influences on social media, c. Ease of Access and Payment Systems, d. Social Environment. Of these factors, promotions and discounts are the most dominant, driving e-commerce purchases. Keywords: factors, consumer behavior, e-commerce.